A 100% Renewable Energy Scenario for the Java-Bali Grid - Matthias Guenther (International Journal of Renewable Energy Development, 2018)
Currently, many countries try to satisfy their energy needs with an increasing usage of renewable resources. The general motivations, with varying weighting in the different countries, are ecological reasons, concerns about energy security, and economical considerations. A for now rather theoretical question, although interesting for opening a long-term perspective, is how an energy supply from exclusively renewable energy resources could look like. This question has to be answered individually for any specific energy supply system. The present paper has the objective to present and evaluate a scenario for an electricity supply only from renewable energy resources for the Java-Bali grid. After designing a load time series for the year 2050 for the Java-Bali grid, a scenario is developed how to cover the load with electricity from renewable energy resources alone. Assumptions about the usable energy sources are made as well as assumptions about the available power plant capacity or energy potential. A specific challenge is the fact that solar energy must be the main source in such a renewable-energy based system, which comes with the need for a large storage capacity to match the power supply at any time with the load. Several possibilities are presented how to bring down the storage capacity: the increment of the installed PV capacity, the usage of bioenergy for seasonal balancing, and the complementation of the proposed short-term storage with an additional long-term storage. The study shows some of the specific challenges that a gradual transformation of the current electricity supply system on Java and Bali into a renewable-energy-based one would face and gives some hints about how to cope with these challenges. Scenarios like the one designed in this study are an important tool for decision-makers who face the task to scrutinize the consequences of choosing between different development paths. Article History: Received: August 15th 2017; Received: October 18th 2017; Accepted: January 14th 2018; Available onlineHow to Cite This Article: Günther, M., Ganal, I. and Bofinger, S. (2018) A 100% Renewable Electricity Scenario for the Java-Bali Grid. Int. Journal of Renewable Energy Development, 7(1), 13-22.https://doi.org/10.14710/ijred.7.1.13-22